BIOMORPHOLOGICAL STRUCTURE OF THE FLORA OF COASTAL ECOSYSTEMS OF DAGESTAN - Z. I. Soltanmuradova; A. A. Teimurov (Юг России: экология, развитие, 2015)
Aim. Analysis of the over all spectrum of life forms of the flora of coastal ecosystems of Dagestan and structural variability of the spectrum indifferent types of plant communities. Methods. The species composition of plant communities and their structural and dynamic features have been determined according to biomorphological indicators during the research and post-processing of the collected material. Based on system of Raunkiera K. (1934) there have been identified five major biomes (fanerofity, hamefity, hemicryptophytes, cryptophytes, terofity) of the flora of coastal ecosystem sof Dagestan, without any further specification. Results. Hemicryptophytes numbering 437 species or 43.52% of the total species composition have been dominated in the flora of coastal ecosystems of Dagestan. In second place terofity (388 species, or 38.64%), the third cryptophytes (80 species or 7.97%). Fanerofity and hanefite are respectively 6.57% and 3.68%. Thus, herbaceous species account or 905 species, or 90.13%. Trees, bushes and shrubsaccountfor a totalof 103 species, or 9.87%. A fairly large percentage of Trofimov can be explained by participation in the studied flora of weedy annuals. Main conclusions. By dominant, similar to the total spectrum of life forms of flora, the position of hemicryptophytes and Trofimov semi-desert and dry steppe plant communities are zonal and climatically determined for this area.